Konstruksi Harmoni Sosial Melalui Interaksi Agama dan Budaya dalam Masyarakat Majemuk - Serlly Della Ressa; Naya Maulidia (Jurnal Ilmu Sosial dan Humaniora, 2026)
Religion and culture are two important elements in human life that have a close relationship in shaping the mindset, behavior, and social life of society. In a pluralistic society with diverse religions, ethnicities, and traditions, the relationship between religion and culture becomes an interesting subject of study due to the processes of interaction, adaptation, and continuous meaning-making. This paper aims to examine the relationship between religion and culture in a pluralistic society, the forms of adaptation between religious values and local culture, as well as the role of both in building social harmony. The method used in this study is a literature review method by analyzing various sources related to religion, culture, pluralistic society, and social relations. The results of the study indicate that religion and culture are not always in a conflicting position; rather, they can interact and adapt to each other within social life. Through attitudes of tolerance, openness, and respect for diversity, religion and culture can become factors that strengthen social relations and create a harmonious society.